2015
DOI: 10.1007/s11999-014-4103-y
|View full text |Cite
|
Sign up to set email alerts
|

How Are Dysplastic Hips Different? A Three-dimensional CT Study

Abstract: Background Surgical correction of acetabular dysplasia can postpone or prevent joint degeneration. The specific abnormalities that make up the dysplastic hip are controversial. Questions/purposes (1) What are the relative size, shape, and orientations of the typical nondysplastic hip? (2) How do these variables differ in the developmentally dysplastic hip? (3) Are there version differences between the acetabuli of dysplastic and nondysplastic hips? (4) Are there pairs of variables in which the change in one is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 74 publications
1
47
0
6
Order By: Relevance
“…This finding is also congruent with available descriptions presented in the literature, surprisingly rare as they are [8,28,29]. The paucity of descriptions of acetabular volume and surface may be associated with the fact that the measurements used are more practical from the viewpoint of surgical treatment, i.e.…”
Section: Wnioskisupporting
confidence: 84%
See 1 more Smart Citation
“…This finding is also congruent with available descriptions presented in the literature, surprisingly rare as they are [8,28,29]. The paucity of descriptions of acetabular volume and surface may be associated with the fact that the measurements used are more practical from the viewpoint of surgical treatment, i.e.…”
Section: Wnioskisupporting
confidence: 84%
“…Fakt ten jest również zgodny z dotychczasowymi, choć zaskakująco rzadkimi, opisami w literaturze [8,28,29]. Niedobór opisów objętości i powierzchni panewki może wiązać się z faktem, że stosowane są pomiary bardziej praktyczne w aspekcie leczenia operacyjnego, tj.…”
Section: Discussionunclassified
“…We found that dysplastic hips are globally deficient in both cartilage and fossa dimensions. A previous three-dimensional CT study described a volumetric decrease of 18% to 19% in dysplastic hips compared with normal hips [5]. Another CTbased study reported a 26% decrease in contact area in dysplastic hips compared with normal hips [12].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies using CT of human hips have measured the contours of the bony acetabulum [13], the relative coverage of the femoral head by the acetabulum in developmental dysplasia of the hip [1,2,5,7], and the contact pressure between the acetabulum and the femoral head [12]. However, these studies have focused on normal and dysplastic hips and did not directly visualize the articular cartilage using MR. Steppacher and colleagues [27] used MR radial sequences to examine protrusio, deep, and retroverted acetabula, finding that retroverted acetabula had smaller cartilage surfaces than deep and protrusio acetabula.…”
Section: Introductionmentioning
confidence: 99%
“…decreased depth. This leads not only to the classic anterior insufficiency but also, potentially, to lateral, posterior, or global deficiency 17 . Even with mild hip dysplasia, the poor coverage of the femoral head, the relative lateralization of the hip center of rotation, and the smaller contact area between the femoral head and the dysplastic acetabulum can produce an asymmetric concentration of force across the hip joint and secondary articular cartilage and labral damage [18][19][20] .…”
Section: Pathomechanism and Natural Historymentioning
confidence: 99%